2018
DOI: 10.1167/iovs.18-24030
|View full text |Cite
|
Sign up to set email alerts
|

Brain-Derived Neurotrophic Factor in Patients With Age-Related Macular Degeneration and Its Correlation With Retinal Layer Thicknesses

Abstract: PURPOSE. To determine brain-derived neurotrophic factor (BDNF) levels in serum and aqueous humor (AH) and to assess the relationship between BDNF levels and retinal layer thicknesses in age-related macular degeneration (AMD). METHODS.A total of 48 AMD patients (AMD group) that was composed of twenty-three nonexudative and 25 exudative patients and 26 control subjects (control group) were included in the study. Serum and AH BDNF levels were assessed by ELISA method. Retinal layer thicknesses were calculated by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 52 publications
(63 reference statements)
1
20
0
Order By: Relevance
“…Note that this clearly pinpoints the need for in vivo studies regarding the NTF mechanism of action, since in vitro studies often rule out the contribution of other (retinal) cells. Additionally, decreased levels of BDNF are also observed in patients with age-related macular degeneration, an eye disease that is not characterized by axonal transport deficits [109]. This again reinforces the statement that alterations in local NTF supply and/or function may be an additional contributing factor in the progression of glaucoma and should not be overlooked.…”
Section: Ntfs As Neuroprotective Therapy In Glaucoma: What Informasupporting
confidence: 54%
“…Note that this clearly pinpoints the need for in vivo studies regarding the NTF mechanism of action, since in vitro studies often rule out the contribution of other (retinal) cells. Additionally, decreased levels of BDNF are also observed in patients with age-related macular degeneration, an eye disease that is not characterized by axonal transport deficits [109]. This again reinforces the statement that alterations in local NTF supply and/or function may be an additional contributing factor in the progression of glaucoma and should not be overlooked.…”
Section: Ntfs As Neuroprotective Therapy In Glaucoma: What Informasupporting
confidence: 54%
“…The formation rate of m-BDNF from pro-BDNF was mediated by the expression of pro-BDNF and tPA-and p11-mediated cleavage process [38]. While previous research mainly focused on the neuroprotective factor m-BDNF [39], the pro-apoptosis characteristic of pro-BDNF in AMD are yet fully illuminated. Pro-BDNF binds to p75 neurotrophin receptor (p75NTR) and coreceptor sortilin with high a nity, thereby triggering apoptosis [40].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have been conducted on serum and AH BDNF levels and ocular disorders like glaucoma, AMD, and diabetic retinopathy. Inanc et al showed that the BDNF level of AH was lower in nonexudative and exudative AMD patients than the controls [6]. The serum and AH BDNF levels were lower in PDR group than in those with NPDR and diabetes without diabetic retinopathy [7].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have been conducted on BDNF levels in the AH and serum in patients with ocular diseases as glaucoma, age-related macular degeneration (AMD), and diabetic retinopathy. Inanc et al found that the BDNF level of AH was lower in non-exudative and exudative AMD groups than the controls [6]. Serum and AH concentrations of BDNF in proliferative diabetic retinopathy (PDR) were lower than in patients with non-proliferative diabetic retinopathy (NPDR) and in diabetics without diabetic retinopathy [7].…”
Section: Introductionmentioning
confidence: 99%